Effect of propeller wash on scour at quay structures - Chen, Xue (2015)
This report aims to study the scour profile produced by a rotating 3-bladed propeller, simulating ships with high-powered engines and large propellers, with the presence of a sloping quay structure. Experiments were conducted with controlled variables to investigate the influence of x, horizontal distance from the toe of slope to the location of the propeller. The impact of different offset ratio y0/Dp, where y0 being the offset height and Dp being the diameter of the propeller, has on the scour profile. Temporal evolution of scouring process along longitudinal direction was analyzed and compared with scouring process in unconfined condition where no sloping quay structures are present. The scour profile consisted of 2 scour holes, with a small one being directly underneath the propeller and a primary one being downstream of the propeller. Both scour holes were asymmetrical about the centerline of the propeller in the longitudinal direction due to the consistent direction of the rotation of the propeller. Both x and y0/Dp had great influence on the scour profile at the asymptotic stage. There was a range of x, where the scouring impact on the sand bed is maximum. In addition, smaller offset ratio resulted in greater scouring impact on the sand bed.